Intestinal intussusception in pregnant women after gastric bypass: Case report - Trevisane, Felipe Grion; Ferrari, Tiago; Stefano, Eduardo Henrique; Hahn, Guilherme Telles; Trevisane, Nathalia Grion [UNESP]; Felipe, Daniele Fernanda; Ferrari, Ariana (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2021)
Worldwide, it is estimated that approximately 634,897 people undergo bariatric procedures each year, with vertical gastrectomy and gastric bypass, representing 53.6% and 30%, respectively. Among operated patients, approximately half are women of reproductive age. In adults, intussusception is typically due to a pathological site in the intestine, which can be malignant in more than half of cases. Intestinal intussusception is rare in adults, representing 1 to 5% of mechanical intestinal obstructions. Intussusception in pregnant women after gastric bypass is a very rare pathology of unknown origin with high power of injury and injury to organs and systems. Its clinical manifestations are like acute obstructive abdomen, but in pregnant women it is difficult to make an early diagnosis. This case report presents a 38-year-old patient, a 22-week pregnant woman, with severe abdominal pain accompanied by vomiting in large quantities for 1 day, a history of gastric bypass for 4 years. The diagnosis of intestinal intussusception was possible after the seventh day of hospitalization with the aid of an image exam - MRI. Surgical treatment is indicated to correct the case. He developed septic shock requiring prolonged hospitalization in an ICU bed, being discharged after 27 days of hospitalization.
Keywords: Gastric bypass; Gestation; Intussusception; Videolaparoscopy